Compromiso y Ética en la Sociedad de la Información - Reyes, Román (Nómadas. Critical Journal of Social and Juridical Science, 2017)
Commitment is complicity and dialogue, but it is also generosity. It is recognition of the other (as subject) and of the other (as object), not so much as exclusion denial as objectification of identity, as self-affirmation of the self as own self. Only can pronounce the word "you" who has risked, who has been trapped by the other in his/its environment (losing, if necessary, his native reference), who has recognized in that other the echo/registration of his/its eventual demonstration/donation, the critical mirror/labile of the own image, of the painting/picture (Bild) that one believes to have put, with caution, in circulation. For that, we create our own images of things in orderthings exist, in order things assume their autonomy.